Lessons Learned: Organizing Knowledge in the Friesian Dairy Cluster (c.1885-1904) - Molema, Marijn (TSEG - The Low Countries Journal of Social and Economic History, 2016)
This paper examines the early years of the Friesian Dairy School and is a case study of how knowledge institutions were integrated into a regional economic cluster. The dairy school was the result of cooperation between people and organisations from the economic and political sectors, which inspired the emergence of an industrial dairy cluster. The school had a difficult start because it was not clear whether higher education was a matter of private or public interest. In the discussions about the funding and direction of the school, we can observe how patterns of cooperation in and between the economic sector and the state were shaped. The study shows how cooperative structures originate in processes of trial and error. Cluster evolution can therefore be driven by both discord and consensus within economic networks. The result of such non-linear and multi-scalar developments ultimately reflect a clear differentiation of tasks between economic actors, the state and knowledge institutions.